Grimm. Season one [videorecording (DVD)] - Hornsby, Russell (Universal Studios Home Entertainment, 2012)
A new drama series inspired by the classic Grimm's Fairy Tales. Portland homicide Detective Nick Burkhardt discovers he is descended from an elite line of criminal profilers known as 'Grimms', charged with keeping balance between humanity and the mythological creatures.